Dysregulation of strongyloidiasis: a new hypothesis. - Genta, R M (1992)
Few other human parasites are associated with such a diverse spectrum of clinical manifestations as Strongyloides stercoralis, yet the basic biological behavior of this unusually versatile worm, particularly with respect to its ability to cause severe disseminated disease in certain hosts, is poorly understood. The current uncritical acceptance of the theory that cell-mediated immunity controls autoinfection has stifled research in other directions. After reviewing what is and is not known about the parasite's behavior in its host, this article explores some of the mechanisms that could be involved in the regulation of the parasite population. Taking the provocative viewpoint that the parasite, not the host, is mainly responsible for the maintenance of a balanced relationship between the two, I propose a new theory that corticosteroids may act on the intraintestinal larvae as molting hormones and directly promote the development of disseminated disease.